Effect of Crotamine, a Toxin of South American Rattlesnake Venom, on the Sodium Channel of Murine Skeletal Muscle - Chang, C. Chiung (1978)
1 Crotamine (0.5 μg/ml) augmented the single twitch response of the rat and mouse isolated diaphragm to direct stimulation and prolonged the time course of contraction. At higher doses (10 to 50 μg/ml), contracture was observed with spontaneous fibrillation. 2 The resting membrane potential of diaphragm was rapidly depolarized to about -50 mV within 5 minutes. No increase of depolarization occurred on prolongation of the incubation time or increase of crotamine concentration from 0.5 μg/ml to 50 μg/ml. The effect was not reversed by washing. 3 Tetrodotoxin, low Na(+) (12 mM), Ca(2+) (10 mM) and procaine (1 mM) prevented the crotamine-depolarization. However, depolarization resumed when crotamine and the antagonists were removed. 4 Low Cl(-) (8.5 mM) and pretreatment with ouabain enhanced depolarization by crotamine. 5 High K(+) (25 to 50 mM) prevented the further depolarization by crotamine and the membrane potential was restored to normal on washout of crotamine with normal Tyrode solution. 6 Effective membrane resistance was decreased by about 50% by crotamine. 7 (24)Na-influx of the rat diaphragm was increased by crotamine. (42)K-influx was slightly increased if tetrodotoxin was also present but was decreased in the absence of tetrodotoxin. 8 No effect on the miniature and evoked endplate potential of the rat diaphragm was observed. Skeletal muscles from frog and chick were not affected. 9 It is inferred that crotamine acts on a molecule regulating the Na(+) - permeability of the Na(+) channel of murine muscles. It is proposed that extracellular K(+) depresses the permeability of the Na(+) channel by acting on the same regulator molecule.